2008
DOI: 10.1111/j.1365-3083.2008.02128.x
|View full text |Cite|
|
Sign up to set email alerts
|

Follicular Lymphoma in a X‐linked Lymphoproliferative Syndrome Carrier Female

Abstract: X‐linked lymphoproliferative (XLP) syndrome is a rare primary immune‐deficiency disorder caused by mutations of the SH2D1A or XIAP genes. Males with the disorder are usually in good health until contracting Epstein–Barr virus (EBV) whereupon the majority of patients die from fulminant infectious mononucleosis, lymphoma or hypogammaglobulinaemia. This report describes a female carrier with an XLP phenotype who was retrospectively identified after her grandson died from the disorder. Subsequent genetic testing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Apart from the risk for recurrence of XLP1 mentioned above, lymphoma was also been reported in SH2D1A female carrier due to nonrandom X-inactivation [ 33 ], suggesting that carrier females in an XLP kindred might be at the risk of developing XLP phenotype and should be monitored for early symptoms. Thus, screening SH2D1A may provide early molecular diagnosis for both XLP1 patients and the potential XLP1 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the risk for recurrence of XLP1 mentioned above, lymphoma was also been reported in SH2D1A female carrier due to nonrandom X-inactivation [ 33 ], suggesting that carrier females in an XLP kindred might be at the risk of developing XLP phenotype and should be monitored for early symptoms. Thus, screening SH2D1A may provide early molecular diagnosis for both XLP1 patients and the potential XLP1 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infection, particularly EBV infection, is an important predisposing factor in HLH. Studies have shown that individuals with immune deficiencies such as X-linked lymphoproliferative syndrome (XLP) are usually asymptomatic before EBV infection, and there is no clear genotype/phenotype correlation [28]. The onset and severity of HLH disease may differ among individuals due to varying exposure to triggering factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both XIAP and cIAP have recently been implicated as having important roles in innate immunity to bacterial infections [105][106][107]. In addition, genetic lack of XIAP has been linked to X-linked lymphoproliferative syndrome (XLP), a condition characterized by an abnormal immune response to infection with the Epstein-Barr virus (EBV) [108,109].…”
Section: The Role Of Iaps In Cancermentioning
confidence: 99%